Bibliometric analysis in journals of Brazilian regional councils of accounting: on environmental accounting and related issues in the period of 2001-2010 - Parente, Edna Ghiorzi Varela (2024)
The main objective of this study was to analyze printed journals available on websites of Brazilian Regional Councils of Accountancy - CRC's - between the years 2001-2010, with related issues to environmental accounting. It is characterized as a Bibliometric study of descriptive character. The subject is justified by being a contemporary theme. It presents qualitative and quantitative data which were analyzed in a complementary way. The results indicate that the online magazines are coming from the CRCs of Rio de Janeiro, Rio Grande do Sul and Paraná. It was concluded that, out of the 233 articles published in CRCRJ only 22 of them present relation with the topic of interest, as well as out of the 247 items found in CRCPR, only 5 of them were identified in the area of environmental accounting and published in 87 CRCRS; 2 of them are articles that address environmental accounting and related subjetcs. It is clear, therefore, that the numbers in the area are not significant and the area can still evolve much in the polls on this subject.